Wheel-Running Modestly Promotes Functional Recovery after a Unilateral Cortical Lesion in Rats - Xiurong Zhao; Jaroslaw Aronowski; Shi-Jie Liu; Timothy Schallert; Jie Zhang; Roger Strong; Zhi-Shuo Ou; Theresa Nguyen; James C. Grotta (Behavioural Neurology)
Background: We aimed to determine whether early or delayed wheel-running (W) after a cortical lesion in rats influences functional recovery and protein expression involving synaptic plasticity.